2015
DOI: 10.1002/lt.24172
|View full text |Cite
|
Sign up to set email alerts
|

Renal function improvement in liver transplant recipients after early everolimus conversion: A clinical practice cohort study in Spain

Abstract: A national, multicenter, retrospective study was conducted to assess the results obtained for liver transplant recipients with conversion to everolimus in daily practice. The study included 477 recipients (481 transplantations). Indications for conversion to everolimus were renal dysfunction (32.6% of cases), hepatocellular carcinoma (HCC; 30.2%; prophylactic treatment for 68.9%), and de novo malignancy (29.7%). The median time from transplantation to conversion to everolimus was 68.7 months for de novo malign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
26
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 34 publications
2
26
0
6
Order By: Relevance
“…Furthermore, and similar to Cholongitas et al,3 patients with renal dysfunction converted to everolimus within the first year after liver transplantation and achieving the greatest renal function improvement, had more frequently received EVR-MPA at baseline compared to patients who converted later: 42.1% versus 13.1%, respectively. 1 In summary, we fully agree on the need to identify renal dysfunction early after liver transplantation. Immunosuppressive regimens based on everolimus combined with tacrolimus minimization have demonstrated efficacy and superior renal function compared to the standard tacrolimus regimen.…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…Furthermore, and similar to Cholongitas et al,3 patients with renal dysfunction converted to everolimus within the first year after liver transplantation and achieving the greatest renal function improvement, had more frequently received EVR-MPA at baseline compared to patients who converted later: 42.1% versus 13.1%, respectively. 1 In summary, we fully agree on the need to identify renal dysfunction early after liver transplantation. Immunosuppressive regimens based on everolimus combined with tacrolimus minimization have demonstrated efficacy and superior renal function compared to the standard tacrolimus regimen.…”
mentioning
confidence: 72%
“…1 We congratulate the authors on the detailed results achieved in their single-center study and would like to respond to their comments. 2 The main objective of our study was to prospectively assess renal function from everolimus initiation onward, and unfortunately, the date of the renal dysfunction diagnosis was not collected.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Bilbao et al 1 did not find any difference in renal function improvement between complete calcineurin inhibitor (CNI) withdrawal and CNI reduction. However, it would be useful to provide the mean trough levels of CNIs in the latter group, as well as to analyze together the patients under everolimus monotherapy and everolimus plus mycophenolic acid.…”
mentioning
confidence: 96%
“…Interestingly, Bilbao et al 1 found that, among the patients with renal dysfunction, those who were treated with everolimus after the first year of LT, improvement in GFR was not found or disappeared at month 12 under everolimus administration. However, the authors did not report if the time between the diagnosis of post-LT renal dysfunction and everolimus initiation was an additional important factor.…”
mentioning
confidence: 99%